Exosomes Secreted from Hypoxia-Preconditioned Mesenchymal Stem Cells Prevent Steroid-Induced Osteonecrosis of the Femoral Head by Promoting Angiogenesis in Rats. (8th April 2021) - Yuan, Na; Ge, Zhaogang; Ji, Wenchen; Li, Jia
Abstract : Recent studies have suggested that exosomes exert similar therapeutic effects to those of mesenchymal stem cells (MSCs) in regenerative medicine and MSCs-derived exosomes exhibit therapeutic effects on steroid-induced osteonecrosis of the femoral head (ONFH). Furthermore, reparative functions of exosomes from MSCs are enhanced by hypoxia treatment of the cells. However, there are no related reports about whether exosomes derived from hypoxia-preconditioned MSCs could show better therapeutic effects on steroid-induced ONFH. In vitro, we investigated the effects of hypoxia precondition on exosomes derived from bone marrow mesenchymal stem cells (BMMSCs) from rats and the proangiogenic ability of exosomes derived from hypoxia-preconditioned BMMSCs. In vivo, we investigated the role of exosomes from hypoxia-preconditioned BMMSCs on angiogenesis and protecting osteonecrosis in a rat ONFH model. We found that the potential of the proangiogenic ability of exosomes derived from hypoxia-preconditioned BMMSCs was higher than exosomes derived from BMMSCs cultured under normoxia. Exosomes derived from hypoxia-preconditioned BMMSCs significantly promoted proliferation, migration, vascular endothelial growth factor (VEGF) expression, and tube formation of human umbilical vein endothelial cells (HUVECs) compared with exosomes derived from BMMSCs cultured under normoxia. Administration of exosomes derived from hypoxia-preconditioned BMMSCs significantly prevented bone loss and increased vessel volume in the femoral head compared with exosomes derived from BMMSCs cultured under normoxia. Taken together, our data suggest that exosomes derived from hypoxia-preconditioned BMMSCs exert better therapeutic effects on steroid-induced ONFH by promoting angiogenesis and preventing bone loss.